2023
DOI: 10.1097/sap.0000000000002807
|View full text |Cite
|
Sign up to set email alerts
|

Has the Increase of Women in Surgical Training Programs Led to a Concomitant Increase in Female Leadership Positions? A 10-Year Analysis

Abstract: IntroductionWomen represent greater than 50% of medical students in America and are becoming increasingly well represented in surgical fields. However, parity at the trainee level has yet to be accomplished, and surgical leadership positions have remained disproportionately biased toward men. To date, there have been no comparisons on the progress within plastic surgery and other surgical specialties. This investigates the gender disparity in resident and leadership representation over the past 10 years within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous research has also shown that the proportion of women in surgical leadership lags behind the number of women training in surgical specialties. However, plastic surgery had the second highest proportion of both female residents and female academic surgical leaders, behind general surgery 19 . In addition, all current female PDs have been appointed in the last 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also shown that the proportion of women in surgical leadership lags behind the number of women training in surgical specialties. However, plastic surgery had the second highest proportion of both female residents and female academic surgical leaders, behind general surgery 19 . In addition, all current female PDs have been appointed in the last 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…The more recent appointments and shorter terms served by female PDs could indicate a trend in hiring more female PDs, as well as represent the increase in women training as plastic surgeons. Between 2008 and 2018, there was a great increase in both the number of women entering plastic surgery training, as well as tremendous growth in the number of women in plastic surgery leadership positions 19 . Previous research has also shown that sex representation in plastic surgery departments favors male surgeons, and that there is a paucity of women in leadership roles 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Women make up more than half of medical doctors in several countries across the globe including the USA, the UK and Australia. Yet, despite gender equity in medical schools (Jena et al , 2015; Radunz et al , 2020; Sexton et al , 2012; Singh et al , 2020; Silver, 2018 and Silver et al , 2017; Temkin, 2020), there is a disparity in surgery and women remain disproportionally underrepresented in leadership positions in surgical specialties including professors, chairpersons or medical school deans (Battaglia et al , 2020; Burdine et al , 2019; Giuffrida et al , 2020; Keane et al , 2021; Olson, et al , 2021; Mueller, 2016; Sexton, 2012; Skinner et al , 2019; Yin et al , 2021). In the USA, studies have shown that 12% of Professors in academic surgery and 25% of surgical faculty are women (Battaglia et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, there is evidence that women practice medicine differently than men. They are more likely to use more patient-centered communication, provide more psychosocial counseling and adhere more closely to clinical guidelines (Yin et al , 2021). Patients treated by female physicians compared with those treated by men within the same hospital have shown significantly improved outcomes, including lower mortality and readmission rates (Tsugawa et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation